The effects of nano-silver and garlic administration during pregnancy on neuron apoptosis in rat offspring hippocampus - Ataei, Maryam Lale (Mashhad University of Medical Sciences, 2014)
OBJECTIVE(S): The aim of this study was to investigate the effects of nano-silver and garlic administration during pregnancy on neuron apoptosis in rat offspring hippocampus. MATERIALS AND METHODS: Fifty pregnant wistar rats were randomly divided into five groups: 1- nano-silver (N.S) group; 30 mg/kg of N.S treated via gavage. 2- Control (C) group, administrated with distilled water via gavage. 3- N.S and garlic (N.S+G) group; N.S (30 mg/kg) and garlic juice (1 ml/100 g) treated via gavage simultaneously. 4- Garlic group (G); garlic juice (1 ml/100 g) administrated via gavage, 5- normal (N) without any intervention. All the interventions were done during pregnancy (21 days). Finally, the brains of rat offspring were removed to use for nano-silver level measurement and TUNEL staining. The mean of TUNEL positive cell numbers per unit area (NA) in different regions of hippocampus were compared in all animal groups. RESULTS: The results revealed a significant increase of hippocampus nano-silver level in N.S and N.S+G groups comparing to N group (P<0.05) and a significant decrease in nano-silver level in N.S+G group comparing to N.S group (P<0.01). The number of TUNEL positive cells in the CA1, CA3, and DG fields of rat offspring hippocampus increased in N.S and N.S+G groups comparing to other ones, and also reduced significantly in N.S+G group comparing to N.S group ((¥) P< 0.01). CONCLUSION: Our results showed that co-administration of nano-silver and garlic during pregnancy may lead to reduce nano-silver induced apoptotic cells in their offspring hippocampus.